Using Steel Fiber Reinforced Concrete (SFRC) as an Alternative to Negative Reinforcement in Continuous RC Slab Panels - H. Aziz, Ali; A. Louis, Mithaq; K. Al-Saraj, Wissam (Iraqi Journal of Civil Engineering, 2013)
This study presents an experimental investigation performed to investigate the using of steel fiber reinforced concrete (SFRC) as an alternative to negative reinforcement in continuous RC thin slab panels. More rational way has been used by replacing negative reinforcement near interior supports by steel fiber reinforced concrete (SFRC). Tests were carried out on four slab panels, simply supported under single point loading. One of which were made fully with NSC, and the others were made partially with SFRC in negative moment zone. Experimental results show that the ultimate load capacity are increased (23% -58%) and the cracking loads are increased (25% -62.5%) for tested specimens strengthened with SFRC, in comparison with the reference specimens. Crack arrest mechanism of steel fibers limits crack propagation, improves the ultimate and tensile strength. So, more practical technique can be concluded from this study and employed in manufacturing of thin slabs.